Engaged ownership : a guide for owners of family businesses - Renkert-Thomas, Amelia, 1962- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2016)
"Successful ownership transition requires effective decision making at the top Engaged Ownership is the definitive owner's guide to the family enterprise. Whether you're taking over a family business, family office, or trust, this book shows you how to work effectively with the management and board to keep the enterprise moving in the right direction. The first guide of its kind written from the owner's perspective, this book is designed to help owners who are truly committed to growing all forms of capital be successful in their role. You'll learn the time-tested process that helps you 'unstick' decision-making, become engaged and effective, and manage the transfer from owner control to shared ownership while minimizing risk. Improve communication and relationships with the board, and ensure that every stakeholder understands your strategies and vision for the future. You'll allay the fears that frequently accompany ownership transfers, and inspire a sense of teamwork that leads to sustainable success generation after generation. As the Baby Boomers retire, business founders and entrepreneurs worldwide are transferring ownership of privately held enterprises to their children in record numbers. It can be a complex and difficult-to-navigate time for everyone involved. This book helps you smooth the way to a successful transition, and transcend the owner's traditionally passive role. Learn to work effectively with management and the board Get everyone on the same page in terms of vision and direction Build relationships that lead to forward-thinking decision making Succeed in the ownership role by bringing your expertise to the fore Ownership transfer often triggers a radical change in family enterprise, and if poorly managed, can turn a business in the wrong direction. Engaged Ownership shows you how to build a dynamic and effective partnership with trustees, board, and management, and become a successful steward of the family's financial, human, social, and operational capital"--
Includes index.
Machine generated contents note: Foreword Preface Acknowledgments Part I: Engaged Ownership: An Introduction Prologue Chapter 1 More at Stake than Money Chapter 2 Achieving Engaged Ownership Chapter 3 Engaged Ownership: Hallmarks and Impediments Part II: Getting Organized Chapter 4 Family Business Roles and Relationships Chapter 5 The Legacy of the Past: Natural Governance, Family History, and Culture Chapter 6 Enumerating Core Capital Chapter 7 Shared Purpose Chapter 8 Vision and Mission Chapter 9 Is It "Good Enough"? Chapter 10 Alternatives to Engaged Ownership Part III: Practicing Engaged Ownership Chapter 11 Forums Chapter 12 Allocating Power among Owners, Board, and Management Chapter 13 Working with Other Forums Chapter 14 Meetings Chapter 15 Policies Part IV: Three Challenges: Hats, Trusts, and Outside Investors Chapter 16 When an Owner Also Runs the Enterprise Chapter 17 When an Owner Is Also a Trustee Chapter 18 Bringing in Outside Investors Chapter 19 Epilogue Appendix: Sample Decision Grid About the Author Index .
Description based on online resource; title from digital title page (viewed on December 28, 2015).
Keywords: Family-owned business enterprises; Small business -- Management; BUSINESS & ECONOMICS / Small Business; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Family-owned business enterprises; Small business -- Management; Electronic books